Knowledge, Attitudes and Barriers Towards Breast Cancer Health Education Among Iraqi Community Pharmacists - H. AL-Behadily, Hasan; F.Al-Tukmagi, Haydar (Iraqi Journal of Pharmaceutical Sciences, 2017)
With the increasing prevalence of breast cancer among female internationally, occupies about 25% of all cases of cancer, with a measured 1.57 million up to date cases in 2012. Breast cancer has turn a most warning to health of female in Iraq, where it is the major cause of death among women after cardiovascular diseases, with a mortality rate of 23% related cancer. Recently there is a crucial requirement to include community pharmacists in health elevation activities to support awareness and early diagnosis of cancer, specially breast cancer. The aim of this study is to assess knowledge, attitude and perceived barriers amongst Iraqi community pharmacists towards health promotion of breast cancer. This study is cross sectional research. A questionnaire was given to pharmacists. The questionnaire comprised from four parts: community pharmacist’s demographics and description of practice; knowledge of signs, symptoms and risk causes; knowledge around breast cancer screening and perceived barriers.300 questionnaires were finished and returned by Iraqi community pharmacists. Mean score of knowledge and screening of breast cancer was 7.9 ± 1.86 and 1.69± 0.33 points respectively, categorizing the overall knowledge and screening of breast cancer among participants as poor level, while mean score for pharmacist attitude was 26.44± 3.86 points, categorizing the overall attitude as favorable. Lack of time was perceived by a great proportion of pharmacists (68.2%) as a major barrier to providing patient education.